Investigation of interaction between ion-beam plasma and processed surface during the synthesis of tantalum diboride and pentaoxide - Yakovin, S.; Zykov, A.; Dudin, S.; Dakhov, A.; Yefymenko, N. (Вопросы атомной науки и техники, 2019)
The paper is devoted to investigation of spatial distributions of ion current density to a sample in technological set-up with magnetron sputtering system and ICP source. The dependence of the ion flux towards the processed surface on the parameters of the deposition process was measured. The following parameters were varied: magnetron discharge power, gas type and pressure, target-sample distance, inductive discharge power, and bias potential applied to the samples. The effect of nonequilibrium heating of the sample surface due to relaxation of kinetic energy of ions, atoms and electrons, as well as energy of exothermic chemical reactions at synthesis of Ta₂O₅ and TaB₂ films is discussed. The influence of sample shape on the ion bombardment is also investigated. Досліджено просторові розподіли щільності іонного струму на зразок у технологічній установці з магнетроном та індукційним джерелом плазми. Виміряно залежності потоку іонів на оброблювану поверхню від параметрів процесу осадження, таких як: потужність магнетрона і індуктивного розряду, тип і тиск газу, потужність, потенціал зсуву на зразок. Обговорюється вплив нерівноважного нагріву поверхні зразка за рахунок релаксації кінетичної енергії іонів, атомів і електронів, а також енергії екзотермічних хімічних реакцій при синтезі плівок Ta₂O₅ і TaB₂. Досліджено вплив форми зразка на іонне бомбардування. Исследованы пространственные распределения плотности ионного тока на образец в технологической установке с магнетроном и индукционным источником плазмы. Измерены зависимости потока ионов на обрабатываемую поверхность от параметров процесса осаждения, таких как: мощность разряда магнетрона и индуктивного разряда, тип и давление газа, мощность, потенциал смещения, подаваемый на образец. Обсуждаются влияние неравновесного нагрева поверхности образца за счет релаксации кинетической энергии ионов, атомов и электронов, а также энергии экзотермических химических реакций при синтезе пленок Ta₂O₅ и TaB₂. Исследовано влияние формы образца на ионную бомбардировку.